"Pra tudo tem os dois lados": implicações ético-políticas da negociação de versões sobre violência numa Escola Municipal de Ensino Fundamental em São Paulo - Mattos, Alexandre Pereira de (2005)
The present research focuses on understanding the meanings of violence at school to educators at school and the strategies taken up in order to deal with it. Formerly, we had taken for granted the several discurvise forms media, demographic data and scientific texts - which contribute for building a concept of violence associated with biological and cultural naturalization. The methodology we took as support is firmly related to the Social Construcionism. Based on this approach, we sought for implying educators from the school where the research took place, in order to potentialize them to construct new meanings and negotiate new versions on the previously existent versions of violence circulating at school. The research was developed in two distinct stages. At first, we registered the speeches on violence arisen as we wander around the school and joined teachers meetings during the Especial Integral Journey (EIJ). This former step helped us on collecting material to compose a report, which supported latter discussions with third grade teachers. Such discussions were held at the second stage of the research under the purpose of compiling a consensual report on the theme. The outcomes obtained at the first stage permitted us to conclude there are multiple and contextual meanings of violence. In addition, we noticed essentialist repertories presented in some speeches, which were associated to the school routine, in favor of excluding and paternalist practices. Teachers of the elementary grades versed their speeches onto the genesis of violence brought up at the family scope. Theachers of the fourth grade considered there is no violence inside school, because students are grown-ups, although they considered as violent the social and economic conditions the students are submitted. Third grade teachers conceived violence as the product of a lacking compass, which is loosen between the necessity of clearer rules at school and the omission of school principal on drawing living rules. They have also found as violent the impossibility of carrying out the primordial school mission, which is to educate. Yet, the analyses brought about by the group discussions, based on the synthesis-report, revealed that the procedures including negotiation of meanings are sensitive to power relations, which may either facilitate or oppose negotiations. We conclude the oppportunities for negotiating senses should not be reduced to single episode, but follow along through the whole researching procedure